Correlation of Initial Plasma Presepsin Level with Pneumonia Severity Index in Children Between 1–5 Years of Age - Mehmood, Tehreem; Riaz, Lubna; Bhatti, Mohammad Awais; Mahmood, Zareen; Chaudhary, Usman (Biological and Clinical Sciences Research Journal, 2025)
Pneumonia remains a leading cause of morbidity and mortality among children aged 1 to 5 years, particularly in low- and middle-income countries such as Pakistan. Early and accurate assessment of disease severity is essential for optimizing management and improving outcomes. The Pneumonia Severity Index (PSI) is a validated clinical tool for risk stratification; however, adjunctive biomarkers may enhance its prognostic utility. Presepsin, a soluble CD14 subtype released during bacterial infections, has emerged as a promising biomarker for assessing infection severity. Objective: To determine the correlation between initial plasma presepsin levels and the Pneumonia Severity Index in children aged 1 to 5 years diagnosed with pneumonia. Methods: This cross-sectional study was conducted over four months in the Pediatric Medicine Department of Shaikh Zayed Medical Complex, Lahore, from 16 May to 16 September 2025. Seventy-nine children aged 1 to 5 years with pneumonia, diagnosed according to World Health Organization criteria, were enrolled using non-probability, consecutive sampling. Plasma presepsin levels were measured within 24 hours of admission using an enzyme-linked immunosorbent assay, with values ≥314 pg/ml considered elevated. Pneumonia severity was assessed using the Pneumonia Severity Index, categorizing patients into low, moderate, and high-risk groups. Data were analyzed using SPSS version 25. Spearman’s correlation coefficient was applied to assess the association between presepsin levels and PSI scores. Results: The mean age of participants was 3.02 ± 1.21 years, with a male predominance (57.0%). Elevated presepsin levels were observed in 65.8% of children. Mean presepsin levels increased progressively with pneumonia severity, measuring 301.4 ± 92.7 pg/ml in the low-risk group, 451.8 ± 134.6 pg/ml in the moderate-risk group, and 712.5 ± 176.9 pg/ml in the high-risk group. A statistically significant positive correlation was found between plasma presepsin levels and PSI scores (Spearman’s r = 0.33, p = 0.003). Conclusion: Plasma presepsin levels are significantly positively correlated with pneumonia severity, as assessed by the Pneumonia Severity Index, in children aged 1 to 5 years. Presepsin may serve as a valuable adjunctive biomarker for early severity stratification of pediatric pneumonia, particularly in resource-limited settings.